Influence Factors for the Choice of a Software Development Methodology - Cristina Venera Geambasu; Iulia Jianu; Ionel Jianu; Alexandru Gavrila (Journal of Accounting and Management Information Systems (JAMIS), 2011)
The success rate of software development projects can be increased by using a methodology that is adequate for the specific characteristics of those projects. Over time a wide range of software development methodologies has been elaborated, therefore choosing one of them is not an easy task. Our research reviews the main categories of development methodologies and then focuses, for a detailed study, on three of them: Rational Unified Process (RUP), Rapid Application Development (RAD) and Extreme Programming (XP). For each methodology it is presented the structure of software life cycle, there are identified the situations in which the methodology can be used successfully and the situations in which it tends to fail. Based on the literature review of software development methodologies and on a series of surveys, published by different researchers, exploring the state of practices in this field, we have identified a number of factors that influence the decision of choosing the most adequate development methodology for a specific project. The methodologies that are subject of this study are evaluated in relation to these factors to find out which development methodology is the most adequate depending on the level of the factors for a specific project. The results of our research are useful for the developers by helping them to identify what software development methodology can be used with success for a specific project.
Keywords: M15; O33; 650; Software development methodology; Rational Unified Process; Rapid Application Development; Extreme Programming; choosing the adequate methodology